150-824:(200-3x(10-2)mũ 2 )
giúp mik
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
1) x3 - 3x2 = 0
<=> x2( x - 3 ) = 0
<=> \(\orbr{\begin{cases}x^2=0\\x-3=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=3\end{cases}}\)
2) 5x( x - 2020 ) - x + 2020 = 0
<=> 5x( x - 2020 ) - ( x - 2020 ) = 0
<=> ( x - 2020 )( 5x - 1 ) = 0
<=> \(\orbr{\begin{cases}x-2020=0\\5x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=2020\\x=\frac{1}{5}\end{cases}}\)
3) ( 3x - 5 )2 = ( x + 1 )2
<=> ( 3x - 5 )2 - ( x + 1 )2 = 0
<=> [ ( 3x - 5 ) - ( x + 1 ) ][ ( 3x - 5 ) + ( x + 1 ) ] = 0
<=> ( 3x - 5 - x - 1 )( 3x - 5 + x + 1 ) = 0
<=> ( 2x - 6 )( 4x - 4 ) = 0
<=> \(\orbr{\begin{cases}2x-6=0\\4x-4=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=3\\x=1\end{cases}}\)
4) ( x2 - 2x )2 - 2( x - 1 )2 + 2 = 0
<=> ( x2 - 2x )2 - 2( x2 - 2x + 1 ) + 2 = 0
<=> ( x2 - 2x )2 - 2x2 + 4x - 2 + 2 = 0
<=> ( x2 - 2x )2 - 2( x2 - 2x ) = 0
<=> ( x2 - 2x )( x2 - 2x - 2 ) = 0
<=> \(\orbr{\begin{cases}x^2-2x=0\\x^2-2x-2=0\end{cases}}\)
+) x2 - 2x = 0 <=> x( x - 1 ) = 0 <=> \(\orbr{\begin{cases}x=0\\x-1=0\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=0\\x=1\end{cases}}\)
+) x2 - 2x - 2 = 0
<=> x2 - 2x + 1 - 3 = 0
<=> ( x2 - 2x + 1 ) = 3
<=> ( x - 1 )2 = ( ±√3 )2
<=> \(\orbr{\begin{cases}x-1=\sqrt{3}\\x-1=-\sqrt{3}\end{cases}}\Leftrightarrow\orbr{\begin{cases}x=1+\sqrt{3}\\x=1-\sqrt{3}\end{cases}}\)
3x-27=4x3 mũ 2
3x-27=4x9
3x-27=36
3x=36+27
3x=63
x=63:3
x=21
824 - 824 : 824 = 823x
824 - 1 = 823x
823 = 823 x
x = 823 : 823
x = 1
( x - 1 ) + 2x - 2 + 3x - 3 = 0
( x - 1 ) + 2x - 2 + 3x = 0 + 3
( x - 1 ) + 2x - 2 + 3x = 3
( x - 1 ) + 2x - 2 + x = 3 : 3
( x - 1 ) + 2x - 2 + x = 1
Làm tiếp nhé
824 - 824 : 824 = 823x
824 - 1 = 823 x
823 x = 823
x = 1
Vậy x = 1
10³ + 2¹⁵
= 1000 + 32768
= 33768
Mà 33768 : 33 = 1023 (dư 9)
Em xem lại đề
trả lời :
= 47
^HT^
TL:
47
HT